THE DIGITAL SIGNIFICANCE OF THE ECONOMIC AND DEVELOPMENT OF THE CONSTRUCTION INDUSTRY (Academicia Globe: Inderscience Research, 2023)
This article analyzes the possibilities and prospects of digitalization of the construction industry in modern economic conditions, and identifies the main problems and prospects of the development of digital construction.